2008
DOI: 10.1519/jsc.0b013e3181634d1e
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combining Elastic and Free Weight Resistance on Strength and Power in Athletes

Abstract: This study was undertaken to determine whether combined elastic and free weight resistance (CR) provides different strength and power adaptations than free weight resistance (FWR) training alone. Forty-four young (age 20 +/- 1 years), resistance-trained (4 +/- 2 years' experience) subjects were recruited from men's basketball and wrestling teams and women's basketball and hockey teams at Cornell University. Subjects were stratified according to team, then randomly assigned to the control (C; n = 21) or experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
104
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 10 publications
10
104
1
2
Order By: Relevance
“…The majority of longitudinal studies that have investigated the effects of combining variable resistance material with freeweights have used rubber bands (2,13,19,21,35). The results have clearly demonstrated that the addition of rubber bands can significantly improve measures of strength and power and those improvements are generally significantly larger than those achieved when using a constant resistance (2,13,35). However, on the basis of the mechanical differences highlighted in the present study it would be inappropriate to generalize the more positive results obtained for rubber bands to the use of chain resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of longitudinal studies that have investigated the effects of combining variable resistance material with freeweights have used rubber bands (2,13,19,21,35). The results have clearly demonstrated that the addition of rubber bands can significantly improve measures of strength and power and those improvements are generally significantly larger than those achieved when using a constant resistance (2,13,35). However, on the basis of the mechanical differences highlighted in the present study it would be inappropriate to generalize the more positive results obtained for rubber bands to the use of chain resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Both the type of band and method of applying rubber-resistance to free-weight exercise can vary (Anderson, Sforzo, & Sigg, 2008;Mcmaster, et al, 2010;Shoepe, et al, 2011). For the SQ, two bands are used on opposite sides of the bar with the free end affixed with choked knots to the squat rack support beams as displayed in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Oppositely, a hypothetical underestimation occurs if the resistance provided by the rubber-band at the start of the concentric phase is used in work volume estimations ( Figure 3B). Using a method of average resistance, as suggested by Anderson et al (2008), would minimize error seen with either extreme, but due to the shape of the length-tension curves of rubber-bands, a systematic underestimate would still occur ( Figure 3C). This underestimate is further exaggerated at lower band lengths when the loading curves are steeper.…”
Section: Discussionmentioning
confidence: 99%
“…In the A et al 16 study, basketball and hockey players experienced a 7 weeks of training with elastic tubes associated with habitual routine of high intensity resistance training (85% of one repetition maximum). In that study both groups performed normal routine of speci c training, but the control group did not perform elastic resistance to the resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…ese kind of material has a progressive resistance as the implement extends, generating more tension when the deformation is larger [12][13][14][15][16] . Previous studies that…”
Section: Introductionmentioning
confidence: 99%